Character Education Discipline in Muhammadiyah Boarding School Dormitory Madrasah Tsanawiyah Muhammadiyah 2 Aimas Based on Local Wisdom - Lestari, Lestari; Pramita, Roni Andri; Anakota, Raisa (Pedagogi : Jurnal Pendidikan dan Pembelajaran, 2025)
Character education based on local wisdom values has become a very urgent issue in the current education system. Law Number 20 of 2003 concerning the National Education System emphasizes that the goal of education is not only to produce intellectually intelligent individuals but also to develop individuals with strong characters. This study aims to analyze the implementation of discipline-based character education in the Madrasah Tsanawiyah Muhammadiyah 2 Aimas dormitory. Using a qualitative approach with a case study method, data were collected through observation, interviews, and documentation. The results of the study indicate that discipline-based character education is implemented through three main stages, namely planning, implementation, and evaluation. Enforcement of discipline in the dormitory includes strict regulations on discipline when entering the dormitory, discipline when entering the dormitory, and discipline when waking up at night. The impact of dormitory-based character education is reflected in alumni testimonies that show increased discipline in waking up in the morning, reading the Qur'an , performing Tahajud and Dhuha prayers , and even being trusted to be the imam of congregational prayers . The results of this study confirm that dormitory-based character education is effective in fostering sustainable positive habits among students.